Whither critique in the world language department?. (July 2017) - Galina, Benjamin J
Language departments have long confronted a disciplinary divide between the study of literature and language. This divide in tenure lines and course content has engendered a similarly deep-seated divide in pedagogical practices. In world language departments, critique often seems confined, for reasons both epistemological and historic, to literature courses. Conversely, in language courses, instructors commonly utilize corrective feedback to train students to think like disciplinary experts. Is it possible then to define a signature pedagogy of the world language department? This article seeks to answer this question by locating a common disciplinary belief in the centrality of language to human experience. Examining the history of critique in teaching and learning in world language departments, the author traces this belief in order to propose a resolution to the departmental divide in the form of a "bilingual critique" that combines elements from both sides.